Selective integration of hierarchical nanostructured energy materials : an effective approach to boost the energy storage performance of flexible hybrid supercapacitors - Gopi, Chandu V. V. Muralee (2021)
High energy density, fast charge–discharge capability, high flexibility, and sustained cycle life are the key challenges in the application of flexible supercapacitors (SCs) in modern electronics. These primary requirements could be accomplished by engineering a new class of current collectors consisting of hierarchical combinations of various active materials. This study reports the selective integration of hierarchical Ni(OH)₂ nanoneedle arrays with NiO–NiCo₂O₄ nanosheet arrays (Ni(OH)₂ NNAs@NiO–NiCo₂O₄ NSAs) on flexible fabric for high-performance electrodes. The novel core–shell-like hetero-nanoarchitectures not only enhance the electrochemical activity and specific surface area but also, more importantly, provide superhighways for the ultrafast transport of electrons and ions. As a battery-type material, the core–shell-like Ni(OH)₂ NNAs@NiO–NiCo₂O₄ NSAs display a high specific capacity of 326.7 mA h g⁻¹ at 2 A g⁻¹ in aqueous 3 M KOH; this value is 1.89, 1.23 and 1.14 times those of NiO–NiCo₂O₄, NiO@NiO–NiCo₂O₄ and Co₃O₄@NiO–NiCo₂O₄ electrodes, respectively. Most importantly, a flexible hybrid SC (FHSC, Ni(OH)₂ NNAs@NiO–NiCo₂O₄ NSAs//graphene-ink) demonstrates a superhigh energy density of 97.1 W h kg⁻¹ and a superior long cycling lifespan with 94.7% retention over 5000 cycles. Utilizing these excellent energy storage properties, the fabricated FHSC operated a multifunction electronic display and light up different colored light emitting diodes for real-time applications.